WH- QUESTIONS IN TEACHING NARRATIVE READING COMPREHENSION TO JUNIOR HIGH SCHOOL STUDENTS - Lestari, Devia; Rufinus, Albert; Bunau, Eusabinus (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2014)
Abstrak : penggunaan wh- question dalam pengajaran teks narasi efektif untuk meningkatkan pemahaman siswa akan teks narasi. Hal ini dibuktikan dari nilai posttest siswa yang lebih baik daripada nilai pretest. Nilai mean pada pretest adalah 43.60 sedangkan nilai mean post test adalah 78.40. interval skor untuk perbandingan nilai pretest dan posttest adalah 34.80. dimana nilai t perbedaan antara kedua test adalah 2.3 yang menggambarkan nilai t dengan pada degress of freedom 0.05 pada level significant 2.042. dari hasil perbandingan kedua test dibuktikan bahwa perbedaan 2.3 lebih tinggi daripada 2.042. hasil ini mengidinkasikan bahawa h0 ditolak dan ha diterima. Pembuktian ini menggambarakan bahwa wh questions efektif untuk meningkatan pemahaman siswa kelas 8 SMP Negeri 1 Mempawah Hulu Kabupaten Landak pada tahun akademik 2011/201 akan teks narasi. Kata kunci : mengajar, membaca, narasi, wh questions Abstract : Using wh- questions in teaching reading narrative text was effective to improve the post-test students’ reading comprehension on narrative text. It was shown by the students’ score which was better than pre-test. The mean score of pre-test is 43.60 while post-test was 78.40. The students’ achievement improved with the interval score of pre-test and post-test was 34.80. The obtain t-value of the differences of the test was 2.3, whereas in the t-table the t-value with 39 degrees of freedom at 0.05 level of significant was 2.042. From this result, we could conclude that the obtained t-value was higher than t-table (2.3 >2.042). It indicated that the null hypothesis (Ho) was rejected, and the alternative hypothesis (Ha) was accepted. It means that the using of wh questions in teaching reading narrative text is effective to improve the students’ reading comprehension by the eighth grade students of SMP Negeri 1 Mempawah Hulu Kabupaten Landak in academic year 2011/2012. Keywords : teaching, reading, narrative, wh questions